Common CD36 SNPs reduce protein expression and may contribute to a protective atherogenic profile - Latisha Love‐Gregory; Richard Sherva; Timothy Schappe; Jian-Shen Qi; Jennifer McCrea; Samuel Klein; Margery A. Connelly; Nada A. Abumrad (2010)
Membrane CD36 functions in the uptake of fatty acids (FAs), oxidized lipoproteins and in signal transduction after binding these ligands. In rodents, CD36 is implicated in abnormal lipid metabolism, inflammation and atherosclerosis. In humans, CD36 variants have been identified to influence free FA and high-density lipoprotein (HDL) levels and to associate with the risk of the metabolic syndrome, coronary artery disease and stroke. In this study, 15 common lipid-associated CD36 single nucleotide polymorphisms (SNPs) were evaluated for the impact on monocyte CD36 expression (protein and transcript) in 104 African Americans. In a subset of subjects, the SNPs were tested for association with monocyte surface CD36 (n = 65) and platelet total CD36 (n = 57). The relationship between CD36 expression and serum HDL and very low-density lipoproteins (VLDLs) levels was also examined. After a permutation-based correction for multiple tests, four SNPs (rs1761667, rs3211909, rs3211913, rs3211938) influenced monocyte CD36 protein and two (rs3211909, rs3211938) platelet CD36. The effect of the HDL-associated SNPs on CD36 expression inversely related to the impact on serum HDL and potential causality was supported by Mendelian randomization analysis. Consistent with this, monocyte CD36 protein negatively correlated with total HDL and HDL subfractions. In contrast, positive correlations were documented between monocyte CD36 and VLDL lipid, particle number and apolipoprotein B. In conclusion, CD36 variants that reduce protein expression appear to promote a protective metabolic profile. The SNPs in this study may have predictive potential on CD36 expression and disease susceptibility in African Americans. Further studies are warranted to validate and determine whether these findings are population specific.